Evaluation of an ivermectin-based attractive targeted sugar bait (ATSB) against Aedes aegypti in Tanzania - Tenywa, FSC; Musa, JJ; Musiba, RM; Swai, JK; Mpelepele, AB; Okumu, FO; Maia, MF (F1000Research, 2022)
Background The control of vector borne arboviral diseases such as Dengue is mainly achieved by reducing human-vector contact and controlling the vectors through source reduction and environmental management. These measures are constrained by labour intensity, insecticide resistance and pro-active community participation. The current study intended to develop and test an ivermectin-based attractive-targeted sugar bait (ATSB) against Aedes aegypti. Methods The 48hour lethal concentration (LC90) of ivermectin against Ae. aegypti was determined through serial dilution experiment where five 30cm x 30cm x 30cm cages were set; into each, a 10% sugar solution treated with ivermectin were introduced. 40 Ae. aegypti were released into each cage and observed for mortality after 4, 8, 24 and 48 hours. The ivermectin-based ATSB was evaluated in a semi field system where ATSB and attractive sugar bait (ASB) were deployed into each compartment of the semi field and 100 female Ae. aegypti were released every day and recaptured the next day through human land catch and Bio-gent sentinel trap. The developed and semi-field tested ATSB was further tested in the field by deploying them in garages. Results The ivermectin 48hr LC90 of male and female Ae. aegypti was found to be 0.03% w/v. In the semi field system, the ATSB significantly reduced a free-flying population of Ae. aegypti within 24 hours (incidence rate ratio (IRR) = 0.62; [95% confidence interval (95%CI); 0.54-0.70] and p-value < 0.001). However, in the field, the ATSBs required the addition of yeast as a carbon dioxide source to efficiently attract Ae. aegypti mosquitoes to feed. Conclusion Ivermectin is an active ingredient that can be used in an ATSB for Ae. aegypti depopulation. However, further research is needed to improve the developed and tested ATSB to compete with natural sources of sugar in a natural environment.